Peran BUMDes Hendrosari dalam Pengembangan Ekonomi Lokal sebagai Upaya Kemandirian Ekonomi Desa - Zhafirah Desvalieta Vianny; Betty Silfia Ayu Utami (CV. ITTC INDONESIA, 2025)
Village economic development is a crucial component of national development strategy, aiming to achieve equitable prosperity and village self-sufficiency. Law Number 6 of 2014 concerning Villages grants authority to villages to manage local potential through Village-Owned Enterprises (BUMDes). This research aims to analyze the role of BUMDes Hendrosari in local economic development as an effort to realize village economic self-sufficiency. The research method used is descriptive qualitative with a literature study approach, through the review of academic literature, policy documents, and publications related to BUMDes management. The results show that BUMDes Hendrosari successfully transformed the village's image from an